The homologation and validation of non-university studies from the perspective of the High Inspection - Gómez Rivas, Fernando A. (Avances en Supervisión Educativa, 2022)
This article addresses the official academic accreditation and recognition of pre-university foreign studies and qualifications under the prism of the High Inspectorate Education Offices (HIEO), conveying the experience from the Office in Madrid, but trying to provide a global perspective of this function. In order to achieve this, the reference regulations are analysed in the first place, starting with the ones with the highest legislative rank, continuing with the regulations that expand the general rule, and finally reviewing the specific administrative rules that affect these procedures. The article then reaches the infinite casuistry produced by the submission of the required documentation and, above all, the disparity and evolution of the educational systems involved. Although an exhaustive analysis of all of them is not possible, the article mentions diverse and curious issues, and a significant example is discussed: the accreditation and recognition of the pre-university studies from the USA. Also related to the records managed by the HIEO, the specific situation of foreign educational institutions in Spain is discussed. These schools represent a variable volume of records processed in the different Offices and is also a set of institutions that has specific characteristics and regulations. Their issues and some of its peculiarities are mentioned. Next, a brief approach to the context and evolution of the HIEO is made, and data and graphs are provided regarding the progression of the number of accreditation and recognition procedures managed by the Offices, both globally and from the local perspective of the Office in Madrid. The graphs will be briefly commented, noting their links to economic factors and other determining circumstances. A penultimate section is devoted to exposing the most recent changes made in these accreditation procedures, in a necessary transformational process whose final implications are still under development. These changes will be connected to the functions entrusted to the HIEO, not only those linked to the accreditation procedures, but also other tasks fulfilled by the Offices, so the global perception of these implications can be pointed out. Lastly, some conclusions are drawn and summarized, and various future perspectives are raised in relation to these accreditation procedures and the HIEO in general.